2017
DOI: 10.1037/xlm0000380
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in face recognition: Neural correlates of repetition and semantic priming in young and older adults.

Abstract: Difficulties in person recognition are among the common complaints associated with cognitive ageing. The present series of experiments therefore investigated face and person recognition in young and older adults. The authors examined how within-domain and cross-domain repetition as well as semantic priming affect familiar face recognition and analyzed both behavioral and event-related brain potential (ERP) measures to identify specific processing stages of age-related deficits. During repetition priming (Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 107 publications
1
12
0
Order By: Relevance
“…Accordingly, compromised face processing may be especially due to changes in early perceptual and/or representational processing stages. This would be in agreement with theories of cognitive aging that suggest declines in perceptual processes and spared semantic knowledge (Craik and Bialystok, 2006;Ofen and Shing, 2013;Wiese et al, 2017).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Accordingly, compromised face processing may be especially due to changes in early perceptual and/or representational processing stages. This would be in agreement with theories of cognitive aging that suggest declines in perceptual processes and spared semantic knowledge (Craik and Bialystok, 2006;Ofen and Shing, 2013;Wiese et al, 2017).…”
supporting
confidence: 91%
“…This pattern is reminiscent of findings by Scott et al (2006; and Tanaka and Pierce (2009): For objects or faces, their participants learned to classify different exemplars at either a basic (e.g., wading bird, owl) or a subordinate level (e.g., egret, snowy owl Cognitive abilities can be differentially affected by age-related declines (Baltes, 1987;Cattell, 1971;Craik and Bialystok, 2006). Older adults may show impaired episodic memory, but preserved semantic memory (Ofen and Shing, 2013, see also Wiese et al, 2017). Intriguingly, our effects in the (Duarte et al, 2006), especially when recognizing newly learned faces , and when source memory was important (Duarte et al, 2006;Li et al, 2004;Swick et al, 2006).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, recent studies suggest that semantic processing may decline with age [ 8 ]. Some studies observed decreased accuracy in semantic tasks which require an explicit use of semantic knowledge in elderly as compared to younger adults [ 9 , 10 , 11 ], whereas other studies found similar accuracy for both age groups (e.g., [ 12 , 13 , 14 ]). This raises the consequential question of whether such potential decline in semantic processing in healthy aging is similar or not (and, if so, to which extent) to the observed deficits in AD.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that younger adults are better in identifying contemporary famous persons [29] led to the assumption that older adults are less adapt in accessing semantic knowledge. However, a recent study showed that semantic priming was intact in older adults [30]. In the current study, we used anonymous images of faces from different age groups and ethnicities that were collected in Dallas, Texas, USA [14].…”
Section: The Current Studymentioning
confidence: 99%